The influence of the microbiological fertilizer – Slavol on cauliflower growth. - Miskoska – Milevska, E.; Najdenovska, O.; Popovski, Z.; Dimovska,D. (My University, 2018)
The microbiological fertilizers play an important role in the yield and quality of crops, having in the same time a reduced impact on environment. The aim of the present study was to evaluate the influence of two methods of application of microbiological fertilizer Slavol on leaf length, leaf width and stomatal density in cauliflower plants. Two different methods of fertilizer application were employed: application through irrigation water (drip irrigation system) and foliar application. The effects of the application methods were evaluated using the following parameters: leaf length and width and stomatal density. A statistical tool (ANOVA test) was employed for data analysis. Foliar and drip irrigation system application of the microbiological fertilizer Slavol determinates an increase in stomatal density and leaf length of cauliflower plants. Also, drip irrigation system application Slavol produced a positive effect on cauliflower leaf length and width. No significant differences were observed between the stomatal density in plants treated by foliar application and plants treated with Slavol through a drip irrigation system.
Keywords: cauliflower, leaf, microbiological fertilizer, stomatal density